Impact of Capital Adequacy on Profitability of Nepalese Commercial Banks - Thapa, Smita (Nepalese Journal of Business, 2024)
This study examines the impact of capital adequacy ratio on the profitability of Nepalese commercial banks. Return on assets and earnings per share are the selected dependent variables. The selected independent variables are capital adequacy ratio, Tier I capital, Tier II capital, non-performing loan, liquidity and total deposit. The study is based on secondary data of 11 commercial banks with 110 observations for the study period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual report of respective commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of capital adequacy ratio on the profitability of Nepalese commercial banks. The study showed that capital adequacy ratio has a positive impact on return on assets and earnings per share. It indicates that increase in capital adequacy ratio leads to increase in return on assets and earnings per share. Similarly, Tier I capital has a positive impact on return on assets and earnings per share. It indicates that increase in core capital leads to increase in return on assets and earnings per share. In contrast, Tier II capital has a negative impact on return on assets and earnings per share. It indicates that increase in supplementary capital leads to decrease in return on assets and earnings per share. Likewise, non-performing loan has a negative impact on return on assets. It indicates that increase in non-performing loan leads to decrease in return on assets. Furthermore, liquidity has a positive impact on return on assets and earnings per share. It indicates that increase in liquidity ratio leads to increase in return on assets and earnings per share. In addition, total deposit has a negative impact on return on assets and earnings per share. It indicates that increase in total deposit leads to decrease in return on assets and earnings per share.